Vertical structure and physical processes of the Madden‐Julian oscillation: Synthesis and summary. Issue 10 (26th May 2015) - Klingaman, Nicholas P.; Jiang, Xianan; Xavier, Prince K.; Petch, Jon; Waliser, Duane; Woolnough, Steven J.
Abstract The "Vertical structure and physical processes of the Madden‐Julian oscillation (MJO)" project comprises three experiments, designed to evaluate comprehensively the heating, moistening, and momentum associated with tropical convection in general circulation models (GCMs). We consider here only those GCMs that performed all experiments. Some models display relatively higher or lower MJO fidelity in both initialized hindcasts and climate simulations, while others show considerable variations in fidelity between experiments. Fidelity in hindcasts and climate simulations are not meaningfully correlated. The analysis of each experiment led to the development of process‐oriented diagnostics, some of which distinguished between GCMs with higher or lower fidelity in that experiment. We select the most discriminating diagnostics and apply them to data from all experiments, where possible, to determine if correlations with MJO fidelity hold across scales and GCM states. While normalized gross moist stability had a small but statistically significant correlation with MJO fidelity in climate simulations, we find no link with fidelity in medium‐range hindcasts. Similarly, there is no association between time step to time step rainfall variability, identified from short hindcasts and fidelity in medium‐range hindcasts or climate simulations. Two metrics that relate precipitation to free‐tropospheric moisture—the relative humidity for extreme daily precipitation and variations in the height and amplitude of moistening with rain rate—successfully distinguish between higher‐fidelity and lower fidelity GCMs in hindcasts and climate simulations. To improve the MJO, developers should focus on relationships between convection and both total moisture and its rate of change. We conclude by offering recommendations for further experiments.